Thermal Injury to Reconstructed Breasts from Commonly Used Warming Devices: A Risk for Reconstructive Failure. Issue 10 (October 2016) - Faulkner, Heather R.; Colwell, Amy S.; Liao, Eric C.; Winograd, Jonathan M.; Austen, William G.
Abstract : Background: Sensation is decreased or absent after breast reconstruction. This leaves reconstructed breasts vulnerable to injury from common household thermal sources such as heating pads and hot water bottles. We sought to categorize these injuries, provide a treatment plan, and prevent these injuries in the future. Methods: A retrospective review of patients who had sustained burns to reconstructed breasts with household devices was performed at a single institution. A PubMed search was performed to identify and summarize articles cataloguing patients who had suffered burns to breast reconstructions. Results: Five patients in our practice were affected. Fifteen articles were identified in the literature search. A total of 40 patients had sustained thermal injury to reconstructed breasts, with the majority being full thickness burns (67.5%). Patients who sustained full thickness burns to reconstructed breasts were more likely to require an operative procedure compared with patients who sustained partial thickness burns ( P = 0.0076). Conclusions: Reconstructed breasts are at risk for injury from commonly used household warming devices and ambient heat from the sun. As a result, patients should be counseled about these risks accordingly, to avoid injury or loss of reconstruction. These injuries require immediate vigilant treatment.